Central and Peripheral Obesity on Severity Knee Osteoarthritis - Efendi, Refangga Lova Nusantara; Wahab, Zulfachmi; Setiawan, M. Riza (Universitas Muhammadiyah Semarang, 2016)
Background: Obesity can affect severity of knee osteoarthritis sufferers. Several studies have examined relationship between obesity and osteoarthritis, but no one has examined the different types of obesity on osteoarthritis, therefore, researchers wanted to know differences of central and peripheral obesity on severity osteoarthritis.Methods: A retrospective studi, with cross-sectional, simple random sampling method, conducted between 1 August 2014 and 30 September 2014 in Semarang City. Samples people > 50 years old. Data were analyzed by rank Spearman and Anova correlation.Results: In this study, 45.7% (n = 32) reported severe osteoarthritis. The results of the statistical test obtained p1 = 0,000 (reject Ho). The correlation coefficient (r) is 0.857 (strong), and the linear pattern is positive. The coefficient of determination (r2) is obtained (0.857) 2 = 0.73 = 73%. And 37.1% (N = 26) reported being obese. p2 = 0.043 (reject Ho). The mean deviation (MD) was 0.048 (not significant) between central obesity and peripheral obesity.Conclusion: Obesity affects severity of knee osteoarthritis. The greater body mass index, greater severity of knee osteoarthritis. 73% of severity of knee osteoarthritis is influenced by obesity, but there is no significant effect between central and peripheral obesity on the occurrence of knee osteoarthritis.